Questioning the veil : open letters to Muslim women - Lazreg, Marnia (Princeton University Press, 2009)
Across much of the world today, Muslim women of all ages are increasingly choosing to wear the veil. Is this trend a sign of rising piety or a way of asserting Muslim pride? And does the veil really provide women freedom from sexual harassment? Written in the form of letters addressing all those interested in this issue, Questioning the Veil examines the inconsistent and inadequate reasons given for the veil, and points to the dangers and limitations of this highly questionable cultural practice. Marnia Lazreg, a preeminent authority in Middle East women's studies, combines her own experiences.